The JCMT BISTRO Survey: Magnetic Fields Align with Orbital Structure in the Galactic Center - Janik Karoly; Derek Ward-Thompson; Kate Pattle; Steven N. Longmore; James Di Francesco; Anthony Whitworth; Doug Johnstone; Sarah Sadavoy; Patrick M. Koch; Meng-Zhe Yang; Ray Furuya; Xing Lu; et al. (The Astrophysical Journal Letters)
We present the magnetic field in the dense material of the Central Molecular Zone (CMZ) of the Milky Way, traced in 850 μ m polarized dust emission as part of the James Clerk Maxwell Telescope B -fields in STar-forming Region Observations survey. We observe a highly ordered magnetic field across the CMZ between Sgr B2 and Sgr C that is strongly preferentially aligned with the orbital gas flows within the clouds of the CMZ. We find that the observed relative orientations are nonrandom at a >99% confidence level and are consistent with models in which the magnetic field vectors are aligned within 30° to the gas flows in 3D. The deviations from aligned magnetic fields are most prominent at positive Galactic longitudes, where the CMZ clouds are more massive, denser, and more actively forming stars. Our observed strongly preferentially parallel magnetic field morphology leads us to hypothesize that in the absence of star formation, the magnetic field in the CMZ is entrained in the orbital gas flows around Sgr A*, while gravitational collapse and feedback in star-forming regions can locally reorder the field. This magnetic field behavior is similar to that observed in the CMZ of the nuclear starburst galaxy NGC 253. This suggests that despite its current low star formation rate, the CMZ of the Milky Way is analogous to those of more distant, actively star-forming, galaxies.